Manajemen Kurikulum Kejuruan dalam Meningkatkan Kompetensi Siswa di SMK Program Keahlian Perhotelan - Fardian Imam Muttaqin; Bambang Sudarsono; Suyatno Suyatno (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The main issue in vocational education is ensuring that the implemented curriculum enhances graduates' competencies in line with industry demands. At SMK Muhammadiyah 1 Moyudan, the primary challenge is aligning the curriculum with the hospitality industry’s needs to ensure graduates acquire relevant skills. This study aims to analyze vocational curriculum management in improving student competencies in the hospitality expertise program. This research employs a qualitative approach with a case study method, collecting data through interviews with the vice principal of curriculum, the head of the expertise program, teachers, and students, as well as curriculum document analysis. The findings indicate that curriculum management at this school involves planning, organizing, implementation, and evaluation tailored to industry needs. The curriculum is designed in collaboration with businesses and industries (DUDI) to ensure the relevance of learning materials to labor market demands. Practical-based learning, such as Field Work Practices (PKL) and competency certification through LSP P1, equips students with the necessary technical skills and soft skills. Evaluation is conducted both formatively and summatively to assess student progress. This study confirms that implementing curriculum management based on industry collaboration contributes to producing competent graduates. The study recommends strengthening cooperation with the hospitality industry, particularly in aspects related to the application of information technology to support learning and competency certification.